2020
DOI: 10.1371/journal.pgen.1008639
|View full text |Cite
|
Sign up to set email alerts
|

Novel frameshift variant in MYL2 reveals molecular differences between dominant and recessive forms of hypertrophic cardiomyopathy

Abstract: Hypertrophic cardiomyopathy (HCM) is characterized by thickening of the ventricular muscle without dilation and is often associated with dominant pathogenic variants in cardiac sarcomeric protein genes. Here, we report a family with two infants diagnosed with infantileonset HCM and mitral valve dysplasia that led to death before one year of age. Using exome sequencing, we discovered that one of the affected children had a homozygous frameshift variant in Myosin light chain 2 (MYL2:NM_000432.3:c.431_432delCT: p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 76 publications
0
16
0
Order By: Relevance
“…Interestingly, here, we also found sexually/developmentally differential expression of Myl2 and Myl9 in correlation with Adnp expression. In this respect, MYL2 is linked to cardiac development and function [51], while MYL9 is involved in smooth muscle and non-muscle cell contractile activity e.g., in the gut and urinary tract [52], with ADNP syndrome children suffering cardiac as well as gastrointestinal problems [17]. Furthermore, a recent study identified Myl9 as highly important for skeletal muscle development [53] as well as to bladder and gastrointestinal smooth muscle contraction, with homozygous deletion leading to megacystis-microcolon-intestinal hypoperistalsis syndrome (MMIHS), a severe disease characterized by functional obstruction in the urinary and gastrointestinal tract [52,54].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, here, we also found sexually/developmentally differential expression of Myl2 and Myl9 in correlation with Adnp expression. In this respect, MYL2 is linked to cardiac development and function [51], while MYL9 is involved in smooth muscle and non-muscle cell contractile activity e.g., in the gut and urinary tract [52], with ADNP syndrome children suffering cardiac as well as gastrointestinal problems [17]. Furthermore, a recent study identified Myl9 as highly important for skeletal muscle development [53] as well as to bladder and gastrointestinal smooth muscle contraction, with homozygous deletion leading to megacystis-microcolon-intestinal hypoperistalsis syndrome (MMIHS), a severe disease characterized by functional obstruction in the urinary and gastrointestinal tract [52,54].…”
Section: Discussionmentioning
confidence: 99%
“…A high restrictive filling pattern and atrial fibrillation incidence were observed ( 19 ). In the same year, the Garg group reported on another missense MYL2 variant (G162R) located in the vicinity of T160 in the C-terminus of RLC ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Homophila database ( http://homophila.sdsc.edu ) reports that the Act genes ( Act57B, Act79B , and Act88F ) and Mlc2 are close matches to the human ACTC1 gene (NP_005150) and MYL2 (NP_000423) genes, respectively. Mutations in both these genes have been associated with familial HCM ( van Waning et al 2019 ; Manivannan et al 2020 ). Next-generation sequencing of an Italian family with HCM revealed an Ala21Val mutation in ACTC1 resulted in myofibrillar disarray causing dis-anchorage of myofilaments ( Frustaci et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%